The Armies of the Streets : The New York City Draft Riots of 1863 - Cook, Adrian (Book collections on Project MUSE., 1974)
In July 1863 New York City experienced widespread rioting unparalleled in the history of the nation. Here for the first time is a scholarly analysis of the Draft Riots, dealing with motives and with the reasons for the recurring civil disorders in nineteenth-century New York: the appalling living conditions, the corruption of the civic government, and the geographical and economic factors that led up to the social upheaval.